Report of a Working Group on Grain Legumes: First meeting, 14-16 July 1995, Copenhagen, Denmark - Gass, T.; Ambrose, M.; Le Guen, J.; Hadjichristodoulou, A.; Blixt, S.; European Cooperative Programme for Plant Genetic Resources (1996)
As part of the European Cooperative Programme for Crop Genetic Resources Networks (ECP/GR), this working group will focus its attention on Cicer, Lens, Lupinus, Phaseolus, Pisum, Glycine, Vicia faba and Vigna. Following discussion of collecting activities, European legume databases, core collections, in situ conservation and links with NGOs, 20 papers are presented which take the form of reviews of national collections. (Abstract © CAB ABSTRACTS, CAB International)